Outcomes of Victorian Prevention and Recovery Care Services: A matched pairs comparison. (December 2021) - Farhall, John; Brophy, Lisa; Reece, John; Tibble, Holly; Le, Long Khanh-Dao; Mihalopoulos, Cathrine; Fletcher, Justine; Harvey, Carol; Morrisroe, Emma; Newton, Richard; Sutherland, Georgina; Spittal, Matthew J; et al.
Objective: In Victoria, Prevention and Recovery Care Services have been established to provide a partial alternative to inpatient admissions through short-term residential mental health care in the community. This study set out to determine whether Prevention and Recovery Care Services are achieving their objectives in relation to reducing service use and costs, fostering least restrictive care and leading to positive clinical outcomes. Methods: We matched 621 consumers whose index admission in 2014 was to a Prevention and Recovery Care ('PARCS consumers') with 621 similar consumers whose index admission in the same year was to an acute inpatient unit and who had no Prevention and Recovery Care stays for the study period ('inpatient-only consumers'). We used routinely collected data to compare them on a range of outcomes. Results: Prevention and Recovery Care Services consumers made less subsequent use of acute inpatient services and, on balance, incurred costs that were similar to or lower than inpatient-only consumers. They were also less likely to spend time on an involuntary treatment order following their index admission. Prevention and Recovery Care Services consumers also experienced positive clinical outcomes over the course of their index admission, but the magnitude of this improvement was not as great as for inpatient-only consumers. This type of clinical improvement is important for Prevention and Recovery Care Services, but they may place greater emphasis on personal recovery as an outcome. Conclusion: Prevention and Recovery Care Services can provide an alternative, less restrictive care option for eligible consumers who might otherwise be admitted to an acute inpatient unit and do so at no greater cost.